Low-frequency signals produced by Northeast Atlantic killer whales (Orcinus orca) - Samarra, Filipa I. P.; Deecke, Volker B.; Miller, Patrick J. O. (The Journal of the Acoustical Society of America, 2016)
Killer whale acoustic behavior has been extensively investigated; however, most studies have focused on pulsed calls and whistles. This study reports the production of low-frequency signals by killer whales at frequencies below 300 Hz. Recordings were made in Iceland and Norway when killer whales were observed feeding on herring and no other marine mammal species were nearby. Low-frequency sounds were identified in Iceland and ranged in duration between 0.14 and 2.77 s and in frequency between 50 and 270 Hz, well below the previously reported lower limit for killer whale tonal sounds of 500 Hz. Low-frequency sounds appeared to be produced close in time to tail slaps, which are indicative of feeding attempts, suggesting that these sounds may be related to a feeding context. However, their precise function is unknown, and they could be the by-product of a non-vocal behavior rather than a vocal signal deliberately produced by the whales. Although killer whales in Norway exhibit similar feeding behavior, this sound has not been detected in recordings from Norway to date. This study suggests that, like other delphinids, killer whales produce low-frequency sounds, but further studies will be required to understand whether similar sounds exist in other killer whale populations. (c) 2016 Acoustical Society of America.